Pengembangan Literasi Digital untuk Anak Usia Dini melalui Media Interaktif - Rejeki, Ayu Srik; Rukhiyati, Iit; listiani, Meri; Nurhayati, Nurhayati; Syamsiah, Syamsiah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
With the rapid development of digital technology, there is a need to improve digital literacy at an early age. Children who grow up in a digital world need basic skills to use devices, understand information, and interact safely and responsibly. Through theoretical analysis and the latest empirical studies, this research attempts to explain the role of interactive media in helping the development of digital literacy in early childhood. The method used is literature research by looking at various relevant scientific publications from 2019 to 2024. The results of the analysis show that interactive media improves basic digital skills, encourages thinking, and engages children in lessons. Interactive media enables multisensory and responsive learning experiences tailored to children's developmental needs. To ensure safe, guided, and age-appropriate use, parents and educators must supervise them. The results show that interactive media, when used in a planned manner and with attention to digital safety aspects, has strategic potential to improve digital literacy in early childhood.